CYTOTOXIC EFFECT OF PLASMA ACTIVATED MEDIUM ON THETREATED BREAST CANCER - Rawnaq Z. Fadhil; Mouruj A. Al aubaydi; Kadhim A. Aadim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to evaluate the effect of plasma activated medium (PAM) on breast cancer cell lines (MCF7 and AMJ13) and compared it to non malignant one (ASCs). The cytotoxic effect of 10,15,20, and 25 min prepared PAM was measured and the results indicated that all cells were influenced in the exposure times (20 and 25)min, especially after 48 hours of incubation with lesser influence on normal cells. Based on the results 20 min was determined as the effective dose on 50% of cancer cells with minimal influence on normal one. Further, tumor necrosis factor-alpha (TNF-α) was assessed and the results indicated reduction in the level of this cytokine after PAM treatment, MCF7 showed significant 2reduction in both incubation intervals while AMJ13 and ASCs significantly varied only after 48hrs.Finally, caspase-9was analyzed to identify the apoptosis route and the obtained data revealed that both MCF7 and AMJ13raisedsignificantlyafter 24 and 48hrs.In contrast, ASC cells revealed non-significant changes in both intervals.